To Study the Correlation of Chronic Obstructive Pulmonary Disease (COPD) Assessment Test, Clinical COPD Questionnaire, and BODE Index in Patients of Stable COPD - Amanpreet Kaur; Amit Goyal; Naveen Pandhi (Assam Journal of Internal Medicine)
Background: Chronic obstructive pulmonary disease (COPD) assessment has emerged as one of the most important parts of COPD treatment. Therefore, a thorough assessment of symptoms is necessary rather than just a measure of dyspnea. Objective: The aim of this study is to assess the disease severity and health status in stable patients of COPD using COPD assessment test (CAT), clinical COPD questionnaire (CCQ) scores, and BODE index and to correlate these indices. Materials and Methods: The study included 100 stable patients suffering from COPD attending outpatient department subjected to CAT, CCQ, and BODE index. Results: CAT and CCQ score correlated significantly (r = 0.52, P < 0.001) and both with the BODE index (r = 0.68; CAT and r = 0.64; CCQ, P < 0.001). COPD severity status and BODE component and forced expiratory volume 1% (FEV1%)-predicted values correlated significantly with individual scores (r = −0.24, CAT; r = −0.41, CCQ; r = −0.72, BODE). Conclusion: An evident negative correlation of FEV1% predicted by CAT and CCQ among study subjects proved both questionnaires as sensitive, simple, and reliable tools not only for early recognition and assessing health status in COPD patients but also for planning appropriate treatment. The BODE index is more objective to assess the disease severity in COPD.